STRATEGI DALAM PENGEMBANGAN POTENSI WISATA ALAM BANTIMURUNG - Faiza Asma, Andi Afifah; Ma'ruf, Adnan; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the Strategy for the Development of Bantimurung Natural Tourism Potential at the Tourism Office of Maros Regency. This type of research used is qualitative. phenomenological type. The data collection technique used is observation, interview. The results of this study indicate that the development strategy carried out by the Tourism Office is the need to improve the quality of human resources, such as increasing awareness in keeping the environment clean. There is provision of special funds by the Tourism Office specifically for Bantimurung tourism to finance and facilitate areas within the Bantimurung area and also to provide adequate facilities and infrastructure in the Bantimurung Nature Tourism area. The strategy for developing the natural tourism potential of Bantimurung at the Tourism Office uses several strategy indicators proposed by Chandler in (Rangkuti Freddy, 2006), namely 1) Human Resources, 2) Funds, 3) Information and Technology, 4) Facilities and Infrastructure.